Pengaruh Strategi Pembelajaran Index Card Match terhadap Aktivitas Belajar Matematika Siswa Kelas V Sekolah Dasar - Mashuri Mashuri; Nurhaswinda Nurhaswinda; Zulfah Zulfah (Lembaga Pengembangan Kinerja Dosen, 2025)
This problem is motivated by the low understanding of students' mathematical concepts in Mathematics subjects at SDN 005 Laggini, Bangkinang District, Kampar Regency City. One solution to overcome this problem is to use a learning modelIndex Card Match. The aim of this research was to determine the effect of the Index Card Match strategy on students' mathematics learning activities in Class V of State Elementary School 005 Laggini, Bangkinang City. This research method is experimental research. The type of research used in this research is pre-test-post test group quasi-experimental design. This research involved fifth grade students at SDN 005 Laggini. The sampling technique used was purposive sampling. The total sample in this study was 63 people who were divided into two classes, namely 32 people from class V A as the experimental class and 31 people from class V B as the control class. The data collected in this study was analyzed using the t-test. Based on the results of statistical calculations, the t-table value was 1.666 and the t-count value was 2.003, which shows that the t-count value was greater than the t table (2.003 > 1.674). Next, based on the independent sample t-test on the p-value or sig. (2-tailed) is 0.005. These results reject the null hypothesis (H0), and the alternative hypothesis (Ha) is accepted. So it can be concluded that the application of learning strategiesIndex Card Match in the experimental class it can influence learning activities better than the application of the lecture method in the control class.